The impact of the FIFA 11+ training program on injury prevention in football players: A systematic review - Barengo, N. C.; Meneses-Echavez, J. F.; Ramirez-Vélez, R.; Cohen, D. D.; Tovar, G. (International Journal of Environmental Research and Public Health, 2014)
The FIFA 11+ is a simple, and easy to implement, sports injury prevention program comprising a warm up of 10 conditioning exercises. The aim of this systematic review was to evaluate the impact of the FIFA 11+ on injury incidence, compliance and cost effectiveness when implemented among football players. MEDLINE, EMBASE and Scopus databases were searched using the search terms "FIFA 11+", "football", "soccer", "injury prevention", and "The 11". The titles and abstracts were screened by two independent reviewers and the data were filtered by one reviewer using a standardized extraction form and thereafter checked by another one. The risk of bias and the methodological quality of the studies were evaluated through the PEDro score and Critical Appraisal Skills Programme (CASP). A total of 911 studies were identified, of which 12 met the inclusion criteria of the review. The FIFA 11+ has demonstrated how a simple exercise program completed as part of warm-up can decrease the incidence of injuries in amateur football players. In general, considerable reductions in the number of injured players, ranging between 30% and 70%, have been observed among the teams that implemented the FIFA 11+. In addition, players with high compliance to the FIFA 11+ program had an estimated risk reduction of all injuries by 35% and show significant improvements in components of neuromuscular and motor performance when participating in structured warm-up sessions at least 1.5 times/week. Most studies had high methodological quality and a low risk of bias. Given the large number of people who play football at amateur level and the detrimental impact of sports injuries on a personal and societal level, the FIFA 11+ can be considered as a fundamental tool to minimize the risks of participation in a sport with substantial health benefits.